Palliative care practice and moral distress during COVID-19 pandemic (PEOpLE-C19 study): a national, cross-sectional study in intensive care units in the Czech Republic - Prokopová, Tereza; Hudec, Jan; Vrbica, Kamil; Stašek, Jan; Pokorná, Andrea; Štourač, Petr; Rusinová, Kateřina; Kerpnerová, Paulína; Štěpánová, Radka; Svobodník, Adam; Maláska, Jan (Critical care, 2022)
BACKGROUND: Providing palliative care at the end of life (EOL) in intensive care units (ICUs) seems to be modified during the COVID-19 pandemic with potential burden of moral distress to health care providers (HCPs). We seek to assess the practice of EOL care during the COVID-19 pandemic in ICUs in the Czech Republic focusing on the level of moral distress and its possible modifiable factors. METHODS: Between 16 June 2021 and 16 September 2021, a national, cross-sectional study in intensive care units (ICUs) in Czech Republic was performed. All physicians and nurses working in ICUs during the COVID-19 pandemic were included in the study. For questionnaire development ACADEMY and CHERRIES guide and checklist were used. A multivariate logistic regression model was used to analyse possible modifiable factors of moral distress. RESULTS: In total, 313 HCPs (14.5% out of all HCPs who opened the questionnaire) fully completed the survey. Results showed that 51.8% (n = 162) of respondents were exposed to moral distress during the COVID-19 pandemic. 63.1% (n = 113) of nurses and 71.6% of (n = 96) physicians had experience with the perception of inappropriate care. If inappropriate care was perceived, a higher chance for the occurrence of moral distress for HCPs (OR, 1.854; CI, 1.057-3.252; p = 0.0312) was found. When patients died with dignity, the chance for moral distress was lower (OR, 0.235; CI, 0.128-0.430; p < 0.001). The three most often reported differences in palliative care practice during pandemic were health system congestion, personnel factors, and characteristics of COVID-19 infection. CONCLUSIONS: HCPs working at ICUs experienced significant moral distress during the COVID-19 pandemic in the Czech Republic. The major sources were perceiving inappropriate care and dying of patients without dignity. Improvement of the decision-making process and communication at the end of life could lead to a better ethical and safety climate. TRIAL REGISTRATION: NCT04910243 .
Keywords: pandemie; Morals; COVID-19; Cross-Sectional Studies; Humans; Czech Republic; smrt; Stress, Psychological; Surveys and Questionnaires; Česká republika; průřezové studie; psychický stres; průzkumy a dotazníky; mravy; postoj zdravotnického personálu; paliativní péče; lidé; Pandemics; Intensive Care Units; Death; Palliative Care; jednotky intenzivní péče; Attitude of Health Personnel